Digital RNA Sequencing of Human Epidermal Keratinocytes Carrying Human Papillomavirus Type 16 E7 - Hua, Chunting; Zhu, Jiang; Zhang, Boya; Sun, Siyuan; Song, Yinjing; van der Veen, Stijn; Cheng, Hao (Frontiers in Genetics, 2020)
High-risk human papillomavirus (HPV) infections are the predominant cause of cervical cancer and its early gene E7 plays an important role in cellular proliferation and cell-cycle progression. While tremendous progress has been made in exploring the molecular mechanisms in late tumorigenesis, many pathways showing how HPV deregulates host gene expression in early inapparent infections and early tumorigenesis still remain undefined. Digital RNA sequencing was performed and a total of 195 differentially expressed genes were identified between the HPV16 E7-transfected NHEKs and control cells (p<0.05, fold-change >2). GO enrichment showed that HPV16 E7 primarily affected processes involved in anti-viral and immune responses, while KEGG pathway analysis showed enrichment of gene clusters of associated with HPV infection and MAPK signaling. Of the differentially expressed genes, IFI6, SLC39A9 and ZNF185 showed a strong correlation with tumor progression and patient survival in the OncoLnc database while roles for AKAP12 and DUSP5 in carcinogenesis and poor prognosis have previously been established for other cancer types. Our study identified several novel HPV16 E7-regulated candidate genes with putative functions in tumorigenesis, thus providing new insights into HPV persistence in keratinocytes and early onset of tumorigenesis.